Mobilization of pdif modules in Acinetobacter: A novel mechanism for antibiotic resistance gene shuffling?. Issue 5 (21st July 2020) - Balalovski, Phillip; Grainge, Ian
Abstract: XerCD‐ dif site‐specific recombination is a well characterized system, found in most bacteria and archaea. Its role is resolution of chromosomal dimers that arise from homologous recombination. Xer‐mediated recombination is also used by several plasmids for multimer resolution to enhance stability and by some phage for integration into the chromosome. In the past decade, it has been hypothesized that an alternate and novel function exists for this system in the dissemination of genetic elements, notably antibiotic resistance genes, in Acinetobacter species. Currently the mechanism underlying this apparent genetic mobility is unknown. Multidrug resistant Acinetobacter baumannii is an increasingly problematic pathogen that can cause recurring infections. Sequencing of numerous plasmids from clinical isolates of A. baumannii revealed the presence of possible mobile modules: genes were found flanked by pairs of Xer recombination sites, called plasmid‐ dif (p dif ) sites. These modules have been identified in multiple otherwise unrelated plasmids and in different genetic contexts suggesting they are mobile elements. In most cases, the pairs of sites flanking a gene (or genes) are in inverted repeat, but there can be multiple modules per plasmid providing pairs of recombination sites that can be used for inversion or fusion/deletion reactions; as many as 16 p dif sites have been seen in a single plasmid. Similar modules including genes for surviving environmental toxins have also been found in strains of Acinetobacter Iwoffi isolated from permafrost cores; this suggests that these mobile modules are an ancient adaptation and not a novel response to antibiotic pressure. These modules bear all the hallmarks of mobile genetic elements, yet, their movement has never been directly observed to date. This review gives an overview of the current state of this novel research field. Abstract : Sequencing of plasmids from Acinetobacter species has revealed what appear to be novel mobile elements; rather than bearing ends characteristic of a transposon, they are flanked by Xer recombination sites in inverted orientation. The presence of multiple (up to 16) recombination sites in a plasmid suggests these are not just multimer resolution sites. This review summarizes what is known so far of these sites and speculates on how they might be mobile.